A systematic literature review of lean manufacturing implementation in manufacturing-based sectors of the developing and developed countries. Issue 3 (28th June 2021) - Maware, Catherine; Okwu, Modestus Okechukwu; Adetunji, Olufemi
Abstract : Purpose: This study aims to comparatively discuss the effect of lean manufacturing (LM) implementation in the manufacturing sectors of developing and developed countries. Design/methodology/approach: An in-depth literature review focused on previous research published between 2015 and March 2020. The papers published by the databases such as Google Scholar, Scopus, ProQuest and Web of Science were used in the study. A total of 63 studies that focused on LM application in manufacturing industries in developing and developed countries were used in the research. Findings: It was observed that LM improves operational performance for manufacturing organizations in developing and developed countries. Small and medium-sized enterprises in both developed and developing countries have difficulties transforming their organizations into lean organizations compared to large enterprises. Furthermore, the review also found that there seems to have been no paper had reported the negative impact of implementing LM in manufacturing industries in developing and developed countries from 2015 to March 2020. Research limitations/implications: The study used research papers written between January 2015 and March 2020 and only considered manufacturing organizations from developed and developing nations. Practical implications: The study provides more insight into LM implementation in developing and developed countries. It gives the LM practices and the implications of applying these practices in manufacturing organizations for developing and developed countries. Originality/value: A preliminary review of papers indicated that this seems to be the first paper that comparatively studies how LM implementation has affected manufacturing organizations in developed and developing countries. The study also assessed the LM practices commonly used by the manufacturing industries in developing and developed countries.